Optimising career adaptability for post-internship students Islamic religious college: the role of work values and social support - Rahmi, Alfi; Afdal; Mudjiran; Netrawati; Iswari, Mega; Engku Kamarudin, Engku Mardiah (Universiti Putra Malaysia, 2024)
A discrepancy between individual values and social support received influences a low degree of career adaptability. This research 122 post-internship students enrolled at the State Islamic Religious College in Sumatra, Indonesia. Work Values Inventory, Multidimensional Scale of Perceived Social Support, and Career Adapt-Abilities Scale (CAAS) were employed as the research instruments using a quantitative design, and multiple regression analysis was adopted to analyse the data. The results showed a significant positive relationship between work values, social support, and career adaptability. Furthermore, the regression model predicted 64.1% of career adaptability, highlighting the synergistic effect of the variables. The results underscored the potential of career counselling interventions in empowering post-internship students by providing essential skills and knowledge for successful career navigation. Implications for career counselling were also discussed, and future analysis was suggested.